Determinant factors of deprassion: a survey among university students - Riaz, Fahad; Amal K, Suleiman; Ismadi, Nur Farhan Izzaty; Choudhry, Fahad Riaz; Munawar, Khadeeja (2017)
We compared the determinant factors of depression; among faculties in university, among junior and senior students, and gender differences among representative samples of faculties in university. Centre for Epidemiological Studies Depression (CES-D) consisting for 20 questions was used to assess the status of well-being of students. A total of 240 students participated and completed the assessment forms. The results were then compared and analyzed using the IBM SPSS Statistics version 21. There was no effect of faculty on depression (p=0.854). The association between year of study and depression was not statistically significant (p≥0.05). Likewise, the association between gender and depression was statistically not significant (p≥0.05). The study revealed absence of statistically significant effect of faculty on depression. It was also found that gender and depression as well as year of study and depression were not statistically significant.